2020
DOI: 10.4149/neo_2020_191014n1034
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA GAS5 promotes natural killer cell cytotoxicity against gastric cancer by regulating miR-18a

Abstract: Natural killer (NK) cells play significant roles in spontaneous antitumor response in multiple cancers, including gastric cancer. Currently, lncRNAs were identified as essential modulators in the development of NK cells via competing for the target miRNA. However, the regulatory mechanism of GAS5 in NK cells remains largely elusive. The expressions of GAS5 and miR-18a in NK cells were measured by qRT-PCR. The killing effects of NK cells were conducted by lactate dehydrogenase (LDH) assay. Detection of IFN-γ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The expression of the NK-specific lncRNA, lnc-CD56, was found to be a positive regulator of CD56 ( 104 ). In addition, the lncRNA, GAS5, could regulate the killing effect of NK cells in several types of cancer ( 105 , 106 ). These results demonstrate the importance of lncRNAs in NK cell function and the antitumor immune response.…”
Section: Lncrna Regulation Of the Time: Focus On Immune Escapementioning
confidence: 99%
“…The expression of the NK-specific lncRNA, lnc-CD56, was found to be a positive regulator of CD56 ( 104 ). In addition, the lncRNA, GAS5, could regulate the killing effect of NK cells in several types of cancer ( 105 , 106 ). These results demonstrate the importance of lncRNAs in NK cell function and the antitumor immune response.…”
Section: Lncrna Regulation Of the Time: Focus On Immune Escapementioning
confidence: 99%
“…In gastric cancer, three miRNAs have been reported to relate to GAS5 , miR-18a [ 95 ], miR-106a-5p [ 63 ] and miR-222 [ 96 ]. In the case of miR-18a, it was reported that GAS5 directly binds to it, inhibiting tumor growth via the stimulation of the activity of natural killer (NK) cells [ 95 ]. On the other hand, GAS5 functions as sponge for miR-106a-5p, inactivating the Akt/mTOR pathway [ 63 ].…”
Section: The Special Case Of Gas5 and Mirnasmentioning
confidence: 99%
“…In the case of miR-544, GAS5 negatively regulates its expression, inhibiting tumor cell proliferation [ 102 ]. GAS5 inhibits cell proliferation also through the miR-544/RUNX3 pathway [ 102 ], where it stimulates NK cell activity and inhibits tumor growth [ 95 ]. In addition, GAS5 and miR-135b reversely correlated and as reported in other tumors, GAS5 over-expression reduces miR-135b expression and, thus, inhibits tumor cell proliferation [ 103 ].…”
Section: The Special Case Of Gas5 and Mirnasmentioning
confidence: 99%
“…The expression of GAS5 augment NK cell cytotoxicity, IFN-γ secretion, and the proportion of CD107a + NK cells by sponging miR-544 to target RUNX3, and thus strengthening the killing effect of NK cells [ 108 ]. Furthermore, lncRNA GAS5 also potentiates the secretion of IFN-γ, TNF-α, as well as cytotoxicity of NK cells against gastric cancer via modulating miR-18a [ 107 ]. Notably, tumor-derived exosomes contain functional lncRNAs can be taken in NK cells for intercellular communication.…”
Section: Introductionmentioning
confidence: 99%